Cognitive Fatigue in Young, Middle-Aged, and Older Adults: A Response Time Distribution Approach. - Gilsoul, Jessica; Libertiaux, Vincent; Depierreux, Frédérique; Collette, Fabienne (Journal of Adult Development, 2024)
Cognitive fatigue arises after a long-lasting task, as attested by increases in reaction times (RTs). However, most studies have focused on young adults. Therefore, we investigated cognitive fatigue through changes in RT distributions in three age groups—young, middle-aged, and older adults—during a 160-min Stroop task. Task duration was divided into four blocks and the ex-Gaussian parameters (μ, σ, τ) were extracted from individual RT distributions in each time block for each item type. The results showed a significant Group effect on μ. Young adults had smaller μ values than the other two groups, meaning that middle-aged and older people performed the whole task slower than young adults. By contrast, τ showed no Group effect but increased with Time-on-Task in middle-aged people. Older adults did not show τ increase with Time-on-Task, which echoes studies showing some resistance to task monotony in this population. Globally, our results showed dissociated age and Time-on-Task effect on the ex-Gaussian parameters, confirming the relevance of this approach in the cognitive fatigue domain. We proposed here that cognitive fatigue affects only the decision component of response production, and that midlife may be a life stage with high sensitivity to cognitive fatigue.